The Help of Social Media In Improving The English Skills of EFL Students - Anandaska, I Gst Pt Ngr Arya Garbha (STKIP AGAMA HINDU SINGARAJA, 2024)
The research analyzes the use of social media for EFL students to learn English in this era where everyone is familiar with the internet. This is also because, during a pandemic situation, most schools implement an online learning system. (Shim & Lee, 2020) said that Covid-19 has significantly changed every sector, including the educational sector. So, the government provided a solution of social distancing to suppress the spread of the covid-19 virus.. Fifteen students from the SPEAK UP English course were participants in this article. The instrument used is through interviews and also provides questionnaires to participants. The researcher will act according to the instrument to obtain data that follows the research objectives. This research aimed to see how useful social media can be in supporting learning progress. The findings of this research indicated that a range of social media commonly used by students is Instagram, blogs, and Twitter. The EFL participants believe that social media can help them enhance their English language skills. Furthermore, Blogs are the most commonly used social media by students in the SPEAK UP English course for learning English and finding information or new vocabulary